Sex Variations in the Oral Microbiomes of Youths with Severe Periodontitis - Ya-Qiong Zhao; Ying-Hui Zhou; Jie Zhao; Yao Feng; Zheng-Rong Gao; Qin Ye; Qiong Liu; Yun Chen; Shao-Hui Zhang; Li Tan; Marie Aimee Dusenge; Jing Hu; et al. (Journal of Immunology Research)
Objective. Periodontitis is an inflammatory disease of microbial etiology caused primarily by dysbiosis of the oral microbiota. Our aim was to compare variations in the composition of the oral microbiomes of youths with severe periodontitis according to gender. Methods. Subgingival plaque samples collected from 17 patients with severe periodontitis (11 males and 6 females) were split for 16S rRNA gene sequencing. The composition, α-diversity, and β-diversity of the patients’ oral microbiomes were compared between the males and the females. Linear discriminant analysis effect size (LEfSe) was used to analyze the specific taxa enriched in the two groups. Functional profiles (KEGG pathways) were obtained using PICRUSt based on 16S rRNA gene sequencing data. Results. The Chao1 index and phylogenetic diversity whole tree were significantly higher in males than in females. The Simpson and Shannon indices were not significantly different between the two groups. β-Diversity suggested that the samples were reasonably divided into groups. The Kruskal-Wallis test based on the relative abundance of species, combined with the LEfSe analysis showed that the dominant bacteria in males were Pseudomonas and Papillibacter, whereas the dominant bacteria in women were Fusobacteriales and Tannerella. KEGG analysis predicted that the variation in the oral microbiome may be related to the immune system in women, whereas immune system diseases were the dominant pathway in men. Conclusion. We found sex-specific differences in the oral microbiome in a sample of youths with severe periodontitis. The differences may be related to changes in immune homeostasis and lead to a better understanding of periodontitis.